DIGIAPEL Interactive Digital Media as a Solution to Improve Digital Literacy of Vocational High School Students - Yusrin Nasrillah; Evania Yafie; Thiessa Krisnanda; Siti Ubaidah; Yunita Asfia (Jurnal Media dan Teknologi Pendidikan, 2025)
The digital literacy of vocational high school students in understanding coating materials still poses challenges in learning practices, as reflected in their low interest in reading and the limited availability of interactive digital media that is interesting and easily accessible. This study aims to develop of DIGIAPEL interactive digital media in supporting the strengthening of vocational high school students' digital literacy in coating materials. DIGIAPEL interactive digital media is designed by integrating the Canva platform as a visual presentation medium and Liveworksheet as a means of learning interactivity. This study uses a research and development approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved 10th grade vocational high school students. Data collection was carried out through questionnaires validated by media and subject matter experts, as well as questionnaires on student responses to the use of DIGIAPEL media. The data were analyzed using integrated qualitative and quantitative descriptive analysis techniques. The results showed that DIGIAPEL media was considered very feasible by media and subject matter experts and received positive responses from students. This media was perceived to have good visual quality, clear navigation structure, and was able to support independent learning and increase student active engagement in the learning process. These findings indicate that the use of DIGIAPEL interactive digital media has the potential to be an effective learning alternative in strengthening the digital literacy of vocational school students. The implications of this study emphasize the importance of developing and utilizing contextual